Anthropogenic Effects on Forest Ecosystems at Various Spatio-Temporal Scales - Michael Bredemeier (The Scientific World Journal)
The focus in this review of long-term effects on forest ecosystems is on human impact. As a classification of this differentiated and complex matter, three domains of long-term effects with different scales in space and time are distinguished: 1- Exploitation and conversion history of forests in areas of extended human settlement 2- Long-range air pollution and acid deposition in industrialized regions 3- Current global loss of forests and soil degradation.